Eksperimen pelaksanaan PdP Dialog Antara Budaya (PPDaB) di dalam kelas / Azarudin Awang and Azman Che Mat - Awang, Azarudin; Che Mat, Azman (2019)
The cultural gap in society needs to be overcome by fostering racial understanding and unity. An effective approach in Teaching and Learning (T&L) occurs when inter-cultural dialogue activities in the classroom are implemented. Dialogues between cultures refer to an interaction that occurs between two different cultural practitioners. The diversity of races, ethnicities and sub-ethnicities in Malaysia makes inter-cultural dialogues an important medium of integration and unity. This study aims to measure level of students' knowledge of popular culture from different ethnic or sub-ethnic groups before and after Pengajaran dan Pembelajaran Dialog Antara Budaya (PPDaB) activities. The study was participated by 71 undergraduate students who enrolled in Ethnic Relations course (CTU 553) at Universiti Teknologi MARA in Terengganu. Based on the data collected from the questionnaires, statistical analysis using mean and sp test (standard deviation) were used to measure students' knowledge, attitudes and perceptions of the given questionnaire items. The findings reveal that implementing PPDaB in the classroom may enhance the level of knowledge, create more positive attitude and interest of the students to a higher scale. Thus, innovation through the implementation of PPDaB in the classroom enhances the understanding, empathy and students' enjoyment of learning.